2021
DOI: 10.5812/aapm.120611
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for Spinal Cord Stimulation Trials and Implants: A Survey Analysis of Practice Patterns

Abstract: Background: Spinal cord stimulation (SCS) is an established treatment modality for neuropathic pain. Published guidelines exist to aid physicians in proper antibiotic use during and after spinal cord stimulation trials and implants. In this brief review, we present and analyze the current antibiotic practice patterns of clinicians. Methods: The study protocol was reviewed and granted an exemption by an Institutional Review Board. The survey queried practice parameters in regards to spinal cord stimulation ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Procedural complications include infection, epidural abscess, epidural hematoma, post-dural puncture headache, and potentially paralysis. Recent studies have shown infection to be the most frequent procedural complication and lead migration to be the most frequent technical complication (3,18). While various complications can arise, proper candidate selection and medical optimization are suggested to allow for greater improvements in pain in a safe, effective manner.…”
Section: History Of Spinal Cord Stimulationmentioning
confidence: 99%
“…Procedural complications include infection, epidural abscess, epidural hematoma, post-dural puncture headache, and potentially paralysis. Recent studies have shown infection to be the most frequent procedural complication and lead migration to be the most frequent technical complication (3,18). While various complications can arise, proper candidate selection and medical optimization are suggested to allow for greater improvements in pain in a safe, effective manner.…”
Section: History Of Spinal Cord Stimulationmentioning
confidence: 99%
“…Interventional procedures vary by complexity and invasiveness, including trigger point injections, epidural steroid injections, sympathetic nerve blocks, radiofrequency ablation, cryoneuroablation, intrathecal drug delivery systems, and spinal cord stimulators, and deep brain stimulation ( 40 - 46 ). Although interventional therapies have associated risks, such as infection, dural puncture, spinal cord trauma, or nerve injury, the significant improvement in quality of life for certain patients makes them attractive treatment options, particularly in those who do not respond well to topical or oral analgesic agents ( 47 - 53 ).…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…Whereas the primary indications for spinal cord stimulation remain failed back surgery syndrome and complex regional pain syndrome, there is a growing list of other indications for use, including chronic intractable back pain without previous surgery where other treatments have failed (3)(4)(5). With increasing indications, it is likely that this treatment option will be increasingly utilized in the future (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%